"After All, They Don't Know Me" Exploring the Psychological Mechanisms of Toxic Behavior in Online Games. Issue 5 (July 2023) - Liu, Yansheng; Agur, Colin
Toxic behavior is commonplace in online games and has negative consequences for players. Although previous studies have illustrated common types and features of in-game toxic behavior, it remains unclear what psychological mechanisms can explain why toxic behavior emerges and evolves in gaming environments. To fill this research gap, guided by Online Disinhibition Effect theory, this study applies a qualitative interview approach to understand when, how, and why people engage in toxic behavior in online games. Specifically, by interviewing players of the game Honor of Kings (a popular Chinese mobile multiplayer online battle arena game), this study illustrates the evolving processes of both verbal and behavioral in-game toxic behavior and identifies six major motivations for players' toxic behavior and three theoretical explanations for how the online gaming environment facilitates players' toxic behavior. Implications of this study on future research are also discussed.